2023
DOI: 10.1088/1361-648x/aced2f
|View full text |Cite
|
Sign up to set email alerts
|

A computational study of 2D group-III ternary chalcogenide monolayer compounds MNTe2 (M, N = In, Ga, Al)

Abstract: First principle calculations of novel 2D group-III ternary chalcogenide monolayer (G3TCM) compounds have been carried out using density functional theory. The 2D hexagonal structure has a honeycomb-like appearance from both the top and bottom views. Both pristine and G3TCM compounds are energetically favourable and have been found to be dynamically stable via phonon calculations. The ab-initio molecular dynamics (AIMD) calculations show the thermodynamical stability of the G3TCM compounds. The G3TCM compounds … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The detailed structure with the color code of the atoms is shown in Figure . The InTe monolayer has shown both thermal and kinematic stability. , After constructing the 3 × 3 supercell of the monolayer, we put one gas molecule of the decomposition remnants of the SF 6 above the monolayer. We considered three possible sites for the initial position of the gas molecule, which are the Te site, the In site, and the hollow site.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The detailed structure with the color code of the atoms is shown in Figure . The InTe monolayer has shown both thermal and kinematic stability. , After constructing the 3 × 3 supercell of the monolayer, we put one gas molecule of the decomposition remnants of the SF 6 above the monolayer. We considered three possible sites for the initial position of the gas molecule, which are the Te site, the In site, and the hollow site.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Our previous study showed that InTe monolayer should be used as photocatalytic material for basic pH values [24]. So, for the enhancement of the photocatalytic behaviour of InTe monolayer, we tried to make artificially 2D hetero bilayer with GeI 2 monolayer.…”
Section: Introductionmentioning
confidence: 99%